LITERASI AL-QURAN SISWA SMP DI JAWA TIMUR - Iswanto, Agus; Oetomo, Setyo Boedi; Noviani, Nur Laili; Khalim, Samidi; Atmanto, Nugroho Eko; Rachmadani, Arnis (Lajnah Pentashihan Mushaf Al-Qur'an, 2018)
The Qurâ€™an is one of the important aspects in fulfilling the required competencies of Islamic Religious Education (PAI). However, little research on Qurâ€™anic literacy has been done, or has never been published. This study was conducted to determine the level of Qurâ€™anic literacy among junior high school students in East Java province. The study took into account 2,267 students, sampled using multistage random sampling. The study showed that in general, the ability to read, copy, and memorize the Qurâ€™an among junior high school students in East Java is of good standards. This proved that the â€œsantriâ€ culture in the communities of East Java has an influence on the above abilities. However, competency in understanding and translating the Qurâ€™an is still low. In fact, the ability to understand or translate the Qurâ€™an is an important indicator of the success of the studentsâ€™ Islamic religious education, especially with regards to the Islamic Religious Education curriculum in junior high school. In addition, the study also found that Qurâ€™an education conducted by parents and organized by the community contribute to the students Qurâ€™anic literacy.